An introduction to performance analysis in sport - O'Donoghue, P. (Routledge, 2015)
Performance analysis has become an essential tool for coaches, athletes, sports organisations and academic researchers. Collecting and interpreting performance data enables coaches to improve their training programmes, athletes to make better tactical decisions, sports organisations to manage teams more effectively, and researchers to develop a better understanding of sports performance. This book is an essential introduction to the fundamental principles of performance analysis of sport and how to develop and operate performance analysis systems.